Ultrasound Guidance for Deep Peripheral Nerve Blocks: A Brief Review - Wadhwa, Anupama (Hindawi Publishing Corporation, 2011)
Nerve stimulation and ultrasound have been introduced to the practice of regional anesthesia mostly in the last two decades. Ultrasound did not gain as much popularity as the nerve stimulation until a decade ago because of the simplicity, accuracy and portability of the nerve stimulator. Ultrasound is now available in most academic centers practicing regional anesthesia and is a popular tool amongst trainees for performance of nerve blocks. This review article specifically discusses the role of ultrasonography for deeply situated nerves or plexuses such as the infraclavicular block for the upper extremity and lumbar plexus and sciatic nerve blocks for the lower extremity. Transitioning from nerve stimulation to ultrasound-guided blocks alone or in combination is beneficial in certain scenarios. However, not every patient undergoing regional anesthesia technique benefits from the use of ultrasound, especially when circumstances resulting in difficult visualization such as deep nerve blocks and/or block performed by inexperienced ultrasonographers. The use of ultrasound does not replace experience and knowledge of relevant anatomy, especially for visualization of deep structures. In certain scenarios, ultrasound may not offer additional value and substantial amount of time may be spent trying to find relevant structures or even provide a false sense of security, especially to an inexperienced operator. We look at available literature on the role of ultrasound for the performance of deep peripheral nerve blocks and its benefits.